Glosarium ekonomi - Basri, Faisal H., 1959 (Rawamangun, Jakarta : Pusat Bahasa, Departemen Pendidikan Nasional, 2004)
English-Indonesian dictionary of economic terms
English and Indonesian
Keywords: Economics -- Terminology; Finance -- Terminology; English language -- Dictionaries -- Indonesian